Oxidation Kinetics of Propane-Air Mixture over NiCo2O4 Catalyst Emitted from LPG Vehicles - Suverna Trivedi; Ram Prasad; S. Chadha (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
This paper describes the kinetics of catalytic air oxidation of propane. The kinetics data were collected in a plug flow tubular reactor. The experiments were performed over the NiCo2O4 catalyst prepared by co-precipitation method followed by calcination at 400 oC. The kinetic data were collected under the following conditions: 200 mg of catalyst, 2.5 % of propane in air, total flow rate of 60 mL/min, and temperature ranges of 130-170 oC. The data were fitted to the power law rate equation. The activation    energy and frequency factor were found to be 59.3 kJ/g mol and 2.9×108 (mol)0.47.L0.53/g cat.h, respectively.